The Interplay of Innovation and Market Structure in German Chemical Industry: Theoretical and Emprical Results on a Dynamic Schumpeter Loop - Torben Schubert (Verein für Socialpolitik, 2010)
This paper investigates the relationship between innovation activities and market structure in German chemical industry. We present a formal model that suggests the existence of a self-enforcing dynamic feedback between market concentration and innovation. This model is tested on the basis of empirical data on German firms from chemical industry taken from the Community Innovation Survey from 2005 (CIS 2005). The results indeed show that a decrease in the number of competitors results in higher innovation activities. The innovation activities in turn tend to reduce the number of competitors. We argue that this feedback can help to explain the industrial dynamics of the chemical industry, which is characterised by high degrees of market concentration and high and concentrated innovation expenditures.
Keywords: O31; D43; C51; 330; Innovation; market structure; competition; Schumpeter Hypothesis; chemical industry